Political Connections, Government Ownership, Loan Growth, and Audit Committee: Determinants of Bank Financial Performance in Indonesia - Istiyah, Iin (Scimadly Publishing, 2025)
This study investigates the effects of political connections, government ownership, and loan growth on the financial performance of banks in Indonesia, with the audit committee serving as a moderating variable. Using a quantitative explanatory approach, data were collected from 32 banks listed on the Indonesia Stock Exchange (IDX) over the period 2017–2021, resulting in 160 firm-year observations. Secondary data were obtained from annual reports and official disclosures, and the analysis was conducted using SSEM-PLS 4.0. The results reveal that political connections and loan growth significantly and positively influence financial performance, whereas government ownership shows a positive but insignificant effect. Furthermore, the audit committee strengthens the positive relationship between political connections and financial performance but does not significantly moderate the effect of government ownership. These findings highlight the importance of lending activities and political connections in driving bank profitability, while also pointing to the ambiguous role of state ownership in balancing commercial and social objectives. This study contributes to the literature on corporate governance and banking performance in emerging markets by providing empirical evidence from Indonesia. The findings also offer practical implications for regulators, bank management, and investors regarding the role of governance mechanisms particularly audit committees in ensuring that political and ownership structures enhance rather than hinder financial performance.